FACTORS AFFECTING CAPITAL STRUCTURE IN AUTOMOTIVE SECTOR COMPANIES IN INDONESIA - ,; ,; ,; ,; , (LUCRUM : Jurnal Bisnis Terapan, 2025)
This study aims to examine the effect of Sales Growth, Asset Structure Growth and Company Size on Capital Structure. The population used in this study is automotive companies listed on the Indonesia Stock Exchange for the period 2018-2021. The sampling technique used purposive sampling with a total of 11 companies. The data analysis technique used is multiple linear regression. The results showed that sales growth, asset structure growth and company size had no effect on capital structure.